Pengaruh Pemanfaatan E-Learning Quipper School Terhadap Hasil Belajar Akuntansi Yang Dimoderasi Oleh Kemandirian Belajar Siswa - Ijah Mulyani Sihotang; Lenni Apriani Hasibuan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Sumatera Utara)
This study aims to determine how the effect of the use of Quipper School e-learning on accounting learning outcomes which are moderated by student learning independence. This research is motivated by low independence and student learning outcomes. This research is a quantitative descriptive research. The research sample was 33 students consisting of two classes at the YPK Medan Vocational School. The data collection techniques used in this study were using tests and questionnaires (questionnaires). The analysis technique uses multiple regression. The results of this study based on multiple regression analysis are (1) There is an effect of the use of Quipper School E-learning on student learning outcomes. (2) There is an effect of learning independence on student learning outcomes and (3) There is an influence of quipper school on student learning outcomes which is moderated by student learning independence